POLA ASUH IBU RUMAH TANGGA DALAM MENANAMKAN DISIPLIN BELAJAR KEPADA ANAKNYA DI PERUMAHAN MUTIARA 2 RW 003 DESA TARAI BANGUN KECAMATAN TAMBANG KABUPATEN KAMPAR - Amy Asmahwati; Aswandi Bahar; Widiastuti ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study aims to find out the most dominant parenting pattern applied by housewife in instilling discipline of learning to her child in Mutiara Housing 2 RW 003 Tarai Bangun Village Tambang Subdistrict Kampar Regency. The formulation of the problem in this research is to know which parenting pattern is the most dominant applied by housewife in instill discipline learn to her child in Mutiara Housing 2 RW 003 Tarai Bangun Village Tambang Sub District Kampar ?. The population in this study were 96 housewives in Mutiara 2 RW 003 Village Tarai Bangun Tambang Sub District Kampar Regency and the sample of this research were 49 housewives in Mutiara Housing 2 RW 003 Tarai Bangun Village Tambang Subdistrict Kampar Regency with critical level 10%, the sample Used is simple random sampling. The instrument of data collection is a questionnaire with 232 statements and after the trial live 222 valid statements to be used as research instruments. Data analysis through Quantitative Descriptive analysis. From the calculation of the percentage of answers obtained by the findings of the research of Household Parenting Patterns in Inculcating Discipline Learning to their Children in Mutiara Housing 2 RW 003 Tarai Bangun Village Tambang Subdistrict Kampar Regency is a style of let slow and safe origins without the pamrih with percentage value (SS + S) 100% This means that the style let me slow home safely and the most selfless style dominantly applied by Housewives in Inculcating Discipline Learning to their Children in Mutiara Housing 2 RW 003 Tarai Bangun Village Tambang District Kampar.Keywords: Parenting, Discipline Learning